Limited Attention and the Demand for Health Insurance - Markus Fels (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We analyze how customers with limited attention value and choose among health plans. We show how the model can accommodate three observations regarding plan choice. First, people tend to overweight the premium and thus underappreciate the value of health insurance. Second, insurance companies may have a strong incentive to reduce quality and to hide these shortcomings in the fine print while attracting customers with insufficiently lower premiums. Finally, the willingness-to-pay for insurance is subadditive creating an incentive for providers to unbundle comprehensive plans. We discuss how these three effects may result in a fundamental dilemma for policy makers.
Keywords: D18; D89; I11; 330